مناهج الإفتاء بين جمعية نهضة العلماء والجمعية المحمدية في إندونيسيا من فترة ما بين عام 1985م-2002م : دراسة أصولية مقارنة - هدى، علم (al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2006)
This research studies and compares juristic methods and principles used by Lajnah Bahth al-Masa'il al-Diniyyah (Research Committee of Religious Issues) and Majlis al-Tarjih (Council of Tarjih) in formulating the fatawa that they issued in response to religious problems posed either by the organization members or by other Muslims in Indonesia. The study confines itself to the period 1985 – 2000. Comparative analysis is applied in order to grasp the way both organizations devised these methods and principles in deducing legal rulings. Deductive method is also employed to analyse problems posed to them. The study concludes that the methods used by Majlis alTarjih are manifested in five principles whose formulation was made in an exclusive Meeting (mu'tamar) held in Yogyakarta from 29 December 1954 to 3 January 1955. Another sixteen general principles used in tarjih (giving preference to particular view(s) over others) were defined in Muhammadiyyah Congress in 1990, which all together supplement the slogan “back/return to the Qur’ān and Sunnah and to the opening of the gate of ijtihad”. With regard to the methods devised by Lajnah Bahth of Nahdlatul ‘Ulama’, it simply refers to opinions of Muslim jurists (fuqaha’) and relies on what is written in the fiqh books (al-kutub al-fiqhiyyah) of the four outstanding legal schools (al-madhahib al-arba'ah). The Committee does not make direct reference to the textual sources of the Shari'ah (al-nusus al-Shari'iyyah, i.e. alQur’an and al-Sunnah, in its argumentation. This sort of method was first formulated in the 28th Congress of Nahdlatul ‘Ulama' which was held in Yogyakarta in 1989, and received official confirmation and recognition in the National Meeting held in Bandar Lampung in 1992.